IMPLEMENTASI KEBIJAKAN PROGRAM BEDAH RUMAH DI DINAS PERUMAHAN, PERMUKIMAN DAN PERTANAHAN KABUPATEN POLEWALI MANDAR - Ahmad Isyraq S; Mahyuddin Ibrahim (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to determine the implementation of housing renovation program policies at the Housing, Settlement and Land Service of Polewali Mandar Regency. The research method used is descriptive research with a qualitative approach. The results showed that the house renovation program in Polewali Mandar Regency was implemented through the standards and objectives of the Home Improvement Program referring to the Regulation of the Minister of Public Works and Public Housing regarding self-help housing stimulant assistance in 2016 and Regent Regulation number 438 of 2016. The implementation of the Home Improvement Program Policy goes well. It is still necessary to increase the distribution of assistance in each district.